2016
DOI: 10.1080/19336896.2016.1211593
|View full text |Cite
|
Sign up to set email alerts
|

Application of mathematical expectation (ME) strategy for detecting low frequency mutations: An example for evaluating 14-bp insertion/deletion (indel) within the bovine PRNP gene

Abstract: ABSTRACT. The detection method based on the mathematical expectation (ME) strategy is fast and accuracy for low frequency mutation screening in large samples. Previous studies have found that the 14-bp insertion/deletion (indel) variants of the 3 0 untranslated region (3 0 UTR) within bovine PRNP gene have been characterized with low frequency (5%) in global breeds outside China, which has not been determined in Chinese cattle breeds yet. Therefore, this study aimed to identify the 14-bp indel within PRNP gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 27 publications
(39 reference statements)
2
45
0
Order By: Relevance
“…On the other hand, the previous studies had reported that the resistant PRNP and PRND polymorphisms had different effects on growth and reproduction traits in different breeds (Lan, Zhao, Li, et al 2012;Ibrahim et al 2015;Yang et al 2016;Li et al 2017). However, the detailed associations between the PRNP polymorphisms and other economical traits remain elusive in cattle.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the previous studies had reported that the resistant PRNP and PRND polymorphisms had different effects on growth and reproduction traits in different breeds (Lan, Zhao, Li, et al 2012;Ibrahim et al 2015;Yang et al 2016;Li et al 2017). However, the detailed associations between the PRNP polymorphisms and other economical traits remain elusive in cattle.…”
Section: Discussionmentioning
confidence: 97%
“…In view of the previous reports, the polymorphisms of PRNP were mostly found to linked to BSE (Sander et al 2005), in addition, some of them were also detected to be associated with some phenotypic traits in cattle (Rzewucka et al 2013;Yang et al 2016), sheep (Brandsma et al 2004;Isler et al 2006;Ioannides et al 2009) and goats (Lan, Zhao, Li, et al 2012;Lan, Zhao, Wu, et al 2012). In detail, the prion octapeptide-repeat polymorphisms were reported to significantly affect milk traits in Latxa dairy sheep (Vitezica et al 2013); In Texel sheep, the PrP genotypes were significantly associated with the litter size and weight at 135 days (Brandsma et al 2004); In the ovine PRNP, the VRQ and ARQ allelic variants (locating on codons 136, 154 and 171) were associated with high scrapie susceptibility, which also led to a significant production loss (Ioannides et al 2009); The 28-bp indel within the promoter region in goat PRNP was associated with production traits in Chinese native breeds (Lan, Zhao, Li, et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a different genotype was considered as an independent variable and litter size was used as the dependent variable using the software program SPSS for correlation analysis. The ANOVA applied to the general liner model (GML) was simplified as follows: Y ij =µ + G i + R j + P k + e, where Y ij is the observation of the litter size, µ is the overall average number of litter size, G i is the fixed effect of genotype or combined genotype, R j is the effect of lambing year, P k is the fixed effect of the parity, and e stands for random residual error (He et al, 2014;Wang et al, 2014;Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for PCR was touchdown PCR, with steps listed as follows: denatured at 95 • C for 5 min, followed by 18 cycles of 95 • C for 30 s, 68 • C declining to 50 • C, decreasing one degree per cycle for 30 s and 72 • C for 20 s, transition from 68 • C to 53 • C for 30 s over the course of 20 cycles, followed by final extension at 72 • C for 10 min. The products were detected by electrophoresis of 2.5 % agarose gel stained with GelRed (Solar-bio Life Science, China), and the products were sequenced only when a given pair of primers had different genotypes (S. H. Yang et al, 2016).…”
Section: Primer Design and Pcr Amplificationmentioning
confidence: 99%
“…During the past few decades, insertion and deletions (indels) have become increasingly popular in the study of animal breeding for understanding the relationship between genotypes and phenotypes. They are an important form of marker-assisted selection (MAS; Xu et al, 2016;Yang et al, 2016;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%